Protection against exploitation of migrant workers - Ali Mohamed, Ashgar Ali; Ahmad, Muhamad Hassan; Eishan Jan, Mohammad Naqib; Ramalingam, Chithra Latha (Allied Academies, 2020)
In the era of globalization, people migrating to foreign countries for better working opportunities become more prevalent compared to the past centuries. At the same time, the international community, especially United Nations (UN) and International Labour Organisation (ILO), come out with several international conventions and legal instruments for the protection of the migrant workers in foreign jurisdictions. At the national level, many States enact various types of laws and regulations relating to employment matters in which some rights of migrant workers are guaranteed in one way or another. Unfortunately, all forms of exploitation of migrant workers across the globe are continuing with the varying degree in different jurisdictions. Accordingly, this paper examines the rights of migrant workers guaranteed under the Malaysian law and proposes that all workers should be treated with equality, fairness, and dignity regardless of whether they are local or migrant. As for the issue of undocumented migrant workers in Malaysia, it is further proposed that the government should take stern action against those who hire undocumented migrant workers and harbour them with accommodations. In the same vein, it should continuously identify undocumented migrant workers for the deportation to their home country. In reducing the reliance on migrant workers, the implementation of the flexible working arrangements for local workers should be given due consideration.